Plant growth regulator and low‐dose herbicide programs for annual bluegrass seedhead suppression in fairway and athletic‐height turf. (17th February 2021) - Peppers, John M.; Brewer, John R.; Askew, Shawn D.
Abstract: Annual bluegrass ( Poa annua L.) seedhead suppression in fairway‐ or athletic‐height turf has become more challenging with the loss of mefluidide, leaving ethephon as the primary annual bluegrass seedhead suppression product. Ethephon programs to suppress annual bluegrass seedheads can cost up to 4.5 times more than that of mefluidide. New options are needed to either improve seedhead suppression programs on fairway‐ or athletic‐height turf or reduce cost associated with use on large areas. Six field research trials were conducted in Blacksburg, VA, to evaluate novel low‐dose herbicide programs and alternate plant growth regulators for mixture with and comparison to ethephon for annual bluegrass seedhead suppression and Kentucky bluegrass ( P. pratensis L.) or creeping bentgrass ( Agrostis stolonifera L.) response. In two separate studies, ethephon applied in December, February, and March suppressed annual bluegrass seedheads 36–39% per day based on area under the progress curve (AUPC). When mixed with ethephon, ethofumesate at 420 g a.i. ha −1, trinexapac‐ethyl at 95 g a.i. ha −1, and prohexadione calcium at 174 g a.i. ha −1 increased seedhead suppression by 34, 14, and 16%, respectively, over that of ethephon alone. Endothall at 140 g a.i. ha −1 also improved seedhead suppression when mixed with ethephon but was too injurious to Kentucky bluegrass and creeping bentgrass turf for commercial use. These studies suggest that low‐dose herbicide treatments or additional plant growth regulator admixtures with ethephon can improve annual bluegrass seedhead suppression in fairway‐ or athletic‐height turf.